FAKTOR-FAKTOR PENYEBAB STUNTING DAN PENCEGAHANNYA DI KELURAHAN SELATPANJANG KOTA KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Saputri, Mely Nia; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Toddlers are part of the age group that is vulnerable to nutritional problems. The problem of stunting is one of the problems faced in the world, especially in poor and developing countries. The purpose of this study was to determine the factors that causingstunting and its prevention in the Selatpanjang Kota,Kecamatan Tebing Tinggi. This type of research is a descriptive quantitative research. The total population in this study was 78 children under five who were stunted, in this study the sampling technique was simple random sampling using the slovin formula, a sample of 65 children under five. Data was collected through primary data using questionnaires and secondary data. The results of the study showed that he most dominant factors were mother’s knowledge, other factors were family economy, clean water and sanitation, food security and health services. It is hoped that prosprective mothers can be prepare for their pregnancy by increasing knowledge about maternal and child nutritional health. Key words: Stunting, factors that cause stunting.